Dementia Care Evidence: Contextual Dimensions that Influence Use in Northern Home Care Centres - Dorothy Forbes; Laurel Strain; Catherine Blake; Shelley Peacock; Wendy Harrison; Terri Woytkiw; Pamela Hawranik; Emily Thiessen; Amy Woolf; Debra Morgan; Anthea Innes; Maggie Gibson (Rural Nurse Organization; Binghamton University, 2015)
Living and working in isolated northern communities pose challenges in using evidence to inform dementia care. Purpose : To better understand the contextual dimensions of two home care centres in two Canadian northern, rural communities that influence the use of evidence from the perspectives of home care providers (HCPs). Sample: All clinical leaders, managers, and home care providers (n=48 FTE) in the two home care centres were sent an information letter outlining the study's purpose, expectations, and benefits and invited to participate in focus groups conducted in two home care centres. Fourteen staff participated in the two focus groups. Method: A qualitative interpretive descriptive approach was used. Semi-structured questions were used to guide the audiotape recorded focus groups. Transcripts were coded using Lubrosky's thematic analysis. Findings: Our findings are described in broad contextual themes (e.g., challenges in using the RAI-HC, availability of resources, relationships in a rural community, leadership, and evaluation) that included both positive and negative contextual dimensions that influenced the use of evidence. Conclusions: Most importantly, reallocated resources are needed in northern home care settings. Challenges in exchanging evidence related to difficult relationships with physicians, clients, and their family caregivers. Leadership and collaboration dimensions were fundamental to establishing a vibrant workplace in which HCPs provided and exchanged evidence-based dementia care.   Keywords: Evidence-based dementia care, northern home care, home care contextual dimensions, knowledge exchange.   DOI:  http://dx.doi.org/ 10.14574/ojrnhc.v15i1.344